Cultures and Organizations / Software of the Mind: Intercultural Cooperation and its Importance for Survival - Harper Collins Business; Hofstede Geert (1994)
The writer reveals the circumstances in which organizational cultures can be managed effectively, and outlines ways of learning intercultural communication which are essential to success in the 1990s and beyond. Preface, Introduction, National Cultures, More Equal than Others, I and We and They, He and She and (s)he, What is Different and What is Dangerous, Pyramids and Machines and Markets and Families, Virtue Versus Truth, Organizational Cultures, From Fad to Management Tool, Implications, Intercultural Encounters, Surviving in a Multicultural World, Appendix: Reading Mental Programs, Glossary, Bibliography, Name and Subject Index.